2013
DOI: 10.1115/1.4025759
|View full text |Cite
|
Sign up to set email alerts
|

Features of Vortex-Induced Vibration in Oscillatory Flow

Abstract: Vortex-induced vibration (VIV) in oscillatory flow is experimentally investigated in the ocean basin. The test flexible cylinder was forced to harmonically oscillate in various combinations of amplitude and period with Keulegan-Carpenter (KC) number between 26 and 178 in three different maximum reduced velocities, URmax=4, URmax=6.5, and URmax=7.9 separately. VIV responses at cross-flow (CF) direction are investigated using modal decomposition and wavelet transformation. The results show that VIV in oscillator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…An experimental investigation of VIV in oscillating flow was performed by Fu et al (2014). These experiments were conducted in the ocean basin at Shanghai Jiao Tong University (SJTU), and consisted of a flexible cylinder being towed horizontally with a prescribed oscillating motion.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…An experimental investigation of VIV in oscillating flow was performed by Fu et al (2014). These experiments were conducted in the ocean basin at Shanghai Jiao Tong University (SJTU), and consisted of a flexible cylinder being towed horizontally with a prescribed oscillating motion.…”
Section: Overviewmentioning
confidence: 99%
“…The relative flow velocity caused by the riser moving back and forth in the water may cause vortex shedding and VIV if the motion amplitude is sufficiently large. VIV of an elastic cylinder in oscillating flow was studied experimentally by Fu et al (2014). They found that the structure vibrated significantly due to vortex shedding, and noted some important differences compared to stationary flow VIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, numerical models could lead to a full characterization of hydrodynamics coefficients in a wide range of Reynolds number and Keulegan-Carpenter number. Fu et al (2014) and Thorsen et al (2016) present interesting results of hydrodynamic forces on a flexible cylinder. Further experiments in order to assess the inertia coefficient would assist towards a deeper understanding of added mass results obtained in the present work.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, Pesce and Fujarra (2000) have also found an added mass value for a flexible cantilever greater than the unity (C a,1 = 1.17). Thorsen et al (2016), analyzing experimental data of a flexible cylinder subjected to an oscillatory flow presented by Fu et al (2014), also found added mass coefficient value greater than the unity (C a = 1.53). It should be recalled that the Sarpkaya charts were obtained for rigid cylinders under oscillatory flow, not for flexible cylinders.…”
mentioning
confidence: 89%